2016
DOI: 10.1186/s13075-016-1158-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of miR-142-3p is related to the pro-inflammatory function of monocyte-derived dendritic cells in SLE

Abstract: BackgroundRecent studies have shown that alterations in the function of dendritic cells (DCs) are involved in the pathogenesis of systemic lupus erythematosus (SLE). However, the mechanism of the alteration remains unclear.MethodsWe cultured monocyte-derived DCs (moDCs) in vitro and examined the cytokines and chemokines in the supernatants of moDCs in negative controls (NC) and SLE patients in active phase. We then profiled microRNAs (miRNAs) of LPS-stimulated moDCs in SLE patients and used real-time PCR to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…The miRNAs could modulate the balance of Th17/Treg in a cell non-autonomous way, that is, through targeting factors important for Th17 and Treg cell development in non-T cells. miR-363, 51 miR-142-3p 61 and miR-223 49 were dysregulated in DCs and could promote Th17 cell differentiation during the pathogenesis of autoimmune diseases. miR-363 suppresses the expression of integrin av, which is an important positive regulator of TGF-b activation.…”
Section: Targets Of Dysregulated Mirnas In Non-t Cellsmentioning
confidence: 99%
“…The miRNAs could modulate the balance of Th17/Treg in a cell non-autonomous way, that is, through targeting factors important for Th17 and Treg cell development in non-T cells. miR-363, 51 miR-142-3p 61 and miR-223 49 were dysregulated in DCs and could promote Th17 cell differentiation during the pathogenesis of autoimmune diseases. miR-363 suppresses the expression of integrin av, which is an important positive regulator of TGF-b activation.…”
Section: Targets Of Dysregulated Mirnas In Non-t Cellsmentioning
confidence: 99%
“…Indeed, in the last few years, miRNAs have emerged as key regulators of inflammation, promoting or suppressing this DC-mediated process [72] (Table 2). Secretion of pro-inflammatory cytokines involved in Crohn's disease [84] miR-142-3p Activation of adaptive immune response mediated by APC [85][86][87] miR-10 NOD2 Maintenance of intestinal homeostasis [88,89] miR-107 Maintenance of intestinal homeostasis Influence the immune response to microbiota [90] miR-223 C/EBPβ Maintenance of homeostasis of the intestinal environment [91] The innate and adaptive responses are highly regulated by cellular and molecular mechanisms through the regulation of the gene expression of specific factors in the cells involved. For this reason, the contribution of miRNAs to inflammatory processes has been amply investigated.…”
Section: Mirnas Regulating the Role Of Dcs In Inflammatory Responsementioning
confidence: 99%
“…This was confirmed by miRNA expression analysis in the pathogenesis of systemic lupus erythematosus (SLE). In fact, the overexpression of miR-142-3p in mo-DCs and cytokines, such as CCL2, CCL5, CXCL8, IL-6, and TNF-α, result in increases in the inflammatory context [85]. Moreover, miR-142-3p, together with miR-24 and miR-30b, can regulate the activation of adaptive immune responses guided by APCs [86,87].…”
Section: Mirnas Regulating the Role Of Dcs In Inflammatory Responsementioning
confidence: 99%
“…Recently, miR-142-3p has been reported to be associated with neuronal diseases. miR-142-3p is the key therapeutic target for repairing sensory function via adenylyl cyclase 9 (AC9) [29]; miR-142-3p in regulating the pro-inflammatory function of moDCs in the pathogenesis of systemic lupus erythematosus (SLE) [30]; miR-142-3p was downregulated in Tuberous sclerosis (TSC) [31]; miR-142-3p was down-regulated in secondary progressive multiple sclerosis (SPMS) [32]; miR-142-3p were aberrantly expressed in peripheral blood mononuclear cells from relapsing remitting multiple sclerosis (RRMS) patients [33]. Although these studies have suggested that miR-142-3p is involved in neuronal development, it remains unclear whether miR-142-3p also plays a role in neuronal regeneration.…”
Section: Discussionmentioning
confidence: 99%